EFFECT OF AMELIORANT ON GROWTH AND YIELD OF RICE AT TIDAL PADDY FIELD - Sri Minarsih; Sri Karyaningsih; Samijan Samijan; Agus Supriyo; Yulis Hindarwati; Nadhifa Husna; Budi Winarto (Indonesian Agency for Agricultural Research and Development, 2021)
Rice (Oryza sativa L.) is the most important and strategic food crop in Indonesia, but low productivity in tidal paddy fields is a serious problem that must be overcome. The application of ameliorant would be worthy to increase the growth and yield of rice in tidal paddy fields. The study aimed to investigate the effect of ameliorant application on growth and yield of rice varieties in tidal paddy fields. The study was arranged in a split plot design with five replications. Rice varieties tested were Inpari 34, Dendang, Inpara 9, Inpari 35, and Ciherang as the main plot, and ameliorant types studied were humic acid, gypsum, zeolite, and organic fertilizer as the subplot. The results showed that the use of different rice varieties and amelioran types significantly increased the growth and yield of rice. Inpara 9 produced 7.6 t.ha-1 dry milled grain (DMG) or increased by 33.3% compared to Ciherang variety. Humic acid application at 25 kg ha-1 increased grain yield by 21.3% higher than that without ameliorant treatment. The best treatment to increase the growth and yield of rice in tidal paddy field was a combination of humic acid 25 kg.ha-1 and Inpari 34 which produced the DMG of 8.6 t ha-1 or 41% higher compared to Ciherang without ameliorant.